2010
DOI: 10.1111/j.1464-410x.2009.09006.x
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic sigmoid neobladder after radical cystectomy: assessment of complications, functional outcomes and quality of life in 82 Japanese patients

Abstract: follow-up of 55 months, after excluding two who died perioperatively. RESULTSThere were 45 early complications in 28 patients, including wound infection in 16, ileus in nine and pyelonephritis in eight, with 19 late complications in 15, including neobladder stone in five, uretero-intestinal stricture in four and entero-urethral stricture in four. Of the 80 patients, 73 could void spontaneously, and daytime and nighttime continence were achieved in 69 and 46, respectively. The mean maximum flow rate, voided vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Furthermore, in our series the favorable voiding status of SNB was confirmed; that is, more than 90% of the patients could void spontaneously, and their post‐void residual urine was less than 25 mL (Table 1). 5,6 Furthermore, daytime and night‐time continence rates in SNB were approximately 85 and 60%, respectively, which appeared to be markedly superior to those in previously reported outcomes in SNB (Table 1). 5–7,9,10 Considering the low compliance of SNB due to the physiological features of the sigmoid colon characterized by a high pressure with powerful contraction of the thick wall, we used a longer sigmoid segment (35–40 cm) than used in other studies, resulting in an increase in the pouch volume and its compliance.…”
Section: Functional Outcomes (Cited From Miyake Et Al5)mentioning
confidence: 52%
See 3 more Smart Citations
“…Furthermore, in our series the favorable voiding status of SNB was confirmed; that is, more than 90% of the patients could void spontaneously, and their post‐void residual urine was less than 25 mL (Table 1). 5,6 Furthermore, daytime and night‐time continence rates in SNB were approximately 85 and 60%, respectively, which appeared to be markedly superior to those in previously reported outcomes in SNB (Table 1). 5–7,9,10 Considering the low compliance of SNB due to the physiological features of the sigmoid colon characterized by a high pressure with powerful contraction of the thick wall, we used a longer sigmoid segment (35–40 cm) than used in other studies, resulting in an increase in the pouch volume and its compliance.…”
Section: Functional Outcomes (Cited From Miyake Et Al5)mentioning
confidence: 52%
“… 5,6 Furthermore, daytime and night‐time continence rates in SNB were approximately 85 and 60%, respectively, which appeared to be markedly superior to those in previously reported outcomes in SNB (Table 1). 5–7,9,10 Considering the low compliance of SNB due to the physiological features of the sigmoid colon characterized by a high pressure with powerful contraction of the thick wall, we used a longer sigmoid segment (35–40 cm) than used in other studies, resulting in an increase in the pouch volume and its compliance. In addition, a small post‐void residual urine, which has been shown to influence continence with a neobladder, 10 may also have contributed to the favorable continence status in our SNB series.…”
Section: Functional Outcomes (Cited From Miyake Et Al5)mentioning
confidence: 52%
See 2 more Smart Citations
“…In addition, 85% of patients had complete daytime incontinence [6]. In another study, Miyake et al reported that the mean maximum flow rate, voided volume, and postvoid residual volume of 82 orthotopic sigmoid NBs were 18.6 mL/s, 345.3 mL, and 24.5 mL, respectively [7]. Zhong et al reported that the mean maximum flow rate, voided volume, and postvoid residual volume of 56 “U-shaped” ileal NBs were 16.2 mL/s, 317.9 mL, and 22.7 mL, respectively [10].…”
Section: Discussionmentioning
confidence: 99%